Assessing area-wide bikeability: A grey analytic network process. (July 2018) - Lin, Jen-Jia; Wei, Yi-Hsuan
Abstract: This article proposes a bikeability assessment method to evaluate zone-based friendliness to biking within an area. The proposed method is developed as an analytic network process (ANP) that contains grey numbers and multiple assessment criteria. The grey ANP is unique in bikeability literature and overcomes the disadvantages of existing assessment methods in the following ways. (1) The ANP framework can manage the interdependences among criteria and zones, (2) the multiple assessment criteria can consider comprehensive perspectives of bikeability, and (3) the grey numbers measure possible ranges of criteria performances and are good at handling various performances within a zone. The application of the method to the bikeability assessment of zones in Daan District, Taipei City, Taiwan not only verifies the effectiveness of the method but also provides action directions to the local administration in developing bike-friendly environments.